Malaysian homestays: the need for standardized regulation / Rohaslinda Ramele Ramli ... [et al.] - Ramele Ramli, Rohaslinda; Yamazaki, Juichi; Ibrahim, Md Najib; Safiee, Lilis Shereena (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
This study aims to clarify regulations used among each type of registered and unregistered Malaysian homestays and to reveal issues arose regarding the implemented regulations. Selected homestays that are established by the government organizations and individuals were investigated to carry out the comparison on each homestay. Host families and persons in charge of the Ministry of Tourism, Arts and Culture (MOTAC), the Ministry of Agriculture (MOA), and the Ministry of Rural and Regional Development (MRRD) were also interviewed. Findings showed that there is only one guideline used for all types of homestays in Malaysia, which is the Malaysia Homestay Registration Guideline, established by MOTAC. MOTAC has also been selected as a leader of homestays in the Southeast Asian countries by the ASEAN Secretariat; therefore, the ASEAN Homestay Standard is also being referred. However, the implementation of this guideline and standard among other homestays unregistered with MOTAC (homestays established by MOA, MRRD, and individuals) is not compulsory, although encouraged, where they may receive equal benefits in term of facilities and promotion. Some issues arose due to the tax regulated by the local authorities, failure on homestays to be registered with MOTAC, and abandoned homestays. This study recommended that the Malaysia Homestay Registration Guideline to be standardized and regulated to all types of homestays, including individuals and unregistered homestays in Malaysia. This is important in order to reduce issues arose involving the homestay industry, providing safety and comfort to the tourists and, to help to develop rural income among host families and the rural community themselves.